An all-endo Approach to Complete Ureteral Duplications Complicated by Ureterocele and/or Vesicoureteral Reflux: Feasibility, Limitations, and Results - A. Calisti; M. L. Perrotta; R. Coletta; C. Olivieri; V. Briganti; L. Oriolo; R. Fabbri (Hindawi Limited, 2011)
Purpose. Totally endoscopic management (all-endo) of patients with a duplicated renal system (DS) associated with severe vesicoureteral reflux (VUR) or obstructive ureterocele (UC) is an attractive alternative to traditional open procedures. The authors discuss feasibility and results of an all-endo approach on a consecutive series of patients. Methods. From 1999 to 2009, all patients with a complete DS associated with UC and/or VUR were proposed for primary all-endo approach. UC puncture was performed using a 3 Fr Bugbee electrode. Deflux (dextranomer/hyaluronic acid copolymer) injection was administered for VUR. The need for secondary surgery was evaluated on followup. Results. Of the 62 patients recruited, 46 were treated using a primary all-endo approach and 16 patients received no treatment. Of the 46 treated patients with 56 affected renal units, 32 (97%) UCs collapsed following puncture and 29 (63%) VURs were resolved or downgraded. Secondary VUR occurred in 13 (39%) renal units. Secondary surgery was performed on 23 (41%) renal units. Conclusion. The all-endo approach for VUR in DS is an effective therapeutic option. UC collapse was achieved by puncture in most of the patients; secondary VUR was the main complication in a small group of extravesical UC.